Early gated SPECT adenosine myocardial perfusion imaging may influence the therapeutic management of patients with coronary artery disease. Issue 4 (April 2015) - Dizdarevic, Sabina; Singh, Nitasha; Nair, Sunil; de Belder, Adam; Ryan, Nicola; Aplin, Mark; Vara, Anil; James, Rachael; McCready, V. Ralph; Peters, A. Michael
Abstract : Aim: The aim of the study was to investigate whether myocardial perfusion imaging at 15 min after injection (T15) is more accurate in detecting coronary artery disease than that at 45 min (T45). Patients and methods: Two-day stress/rest 99m Tc-tetrofosmin gated SPECT was performed at T15 and T45 in 50 patients. Coronary angiography was considered when poststress and resting images were discordant. Tracer washout rates were calculated for the myocardium, liver, and subdiaphragmatic region. Perfusion sum difference scores were derived using QPS software. Results: T15 and T45 were discordant in 18/50 (36%) patients. In 16/18 patients (89%) discordant deficits were more apparent at T15. A total of 13/16 patients underwent coronary angiography, of whom 12 had coronary artery disease. Poststress, but not resting, left ventricular ejection fraction was lower at T15 ( P =0.02). Sum difference scores were higher at T15 [2.2 (1.9)] than at T45 [1.6 (1.7); P <0.05]. Tracer washout rates from the liver [46 (13.3)%] and subdiaphragmatic region [36 (21.3)%] were significant ( P <0.0001), but there was no change in myocardial activity. Conclusion: T15 detected more abnormalities than did T45. The reduction in left ventricular ejection fraction after stress may result from adenosine-induced poststunning at T15. Accordingly, the T15 protocol may be useful in the assessment of hibernating myocardium. Contrasting myocardial and hepatic washout rates may be attributable to differential ABC transporter expression.